CODE SWITCHING USED BY SARAH SECHAN IN "SARAH SECHAN" PROGRAM ON NET TV - NOVI SRIWULANDARI (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2016)
English is an international language in this world, this statement is real, therefore almost every single person in this world is common with English, moreover, each person is capable of speaking and writing two languages well in English and in the mother tongue. The people in those conditions are called bilingual, they usually switch a language to another in their social life, that is code-switching. In this occasion, this research focuses on analyzing code switching used by Sarah Sechan In "Sarah Sechan" Program On NET TV, using a theory of code-switching adopted from Miller (2003), Crystal (1987), Romaine (1992), Sauders (1988), and Skiba (1997). The aims of this research are 1). to describe and analyzes the types of code switching and finding the most dominant of them, and 2). to describe the reasons for Sarah Sechan code switch her language in "Sarah Sechan" program on NET TV.This research uses descriptive qualitative approach whereas the data are collected from the utterances of Sarah Sechan in "Sarah Sechan" program on NET TV in five top video on September 2018 which are analyzed by adopted from the theory of Miller (2003), Crystal (1987), Romaine (1992), Sauders (1988), and Skiba (1997).The result of this research shows that there are three types of code-switching used by Sarah Sechan in "Sarah Sechan" program on NET TV: intra-sentential switching, inter-sentential switching, and tag switching. In detail, there are intra-sentential switchings, inter-sentential switchings, and tags switching. There are several reasons of Sarah Sechan code switch her language: talking about a particular topic, quoting somebody else, showing empathy about something, interjection, repetition used for clarification, expressing group identity, and intention of clarifying the speech content for the interlocutor.This research only analyses types and reasons for code-switching, therefore it will be more interesting for the next researcher to analyze it by using another theory of code-switching. It is suggested for the next researcher to use other object or data such as youtuber or selebgram as the data source.